A new macropterous species of a rarely collected subfamily (Heteroptera, Tingidae, Vianaidinae) - Guidoti, Marcus; Montemayor, Sara I. (Zootaxa, 2016)
Pterovianaida duckensis n. sp., a new macropterous species of the rarely collected subfamily Vianaidinae is here described. The group currently comprises nine species, two of them fossils. Pterovianaida Montemayor and Carpintero is a recent monotypic genus described for a macropterous species collected in Peru. Here, a new macropterous species of Pterovianaida is described, and characters of the head, pronotum and hemelytra distinguish this species from the type species. This is the first record of a macropterous Vianaidinae for Brazil. A key to all extant species of this subfamily is provided.